2016
DOI: 10.1093/ptep/ptw050
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement in four-dimensional SU(3) gauge theory

Abstract: We investigate the quantum entanglement entropy for the four-dimensional Euclidean SU(3) gauge theory. We present the first non-perturbative calculation of the entropic c-function (C(l)) of SU(3) gauge theory in lattice Monte Carlo simulation using the replica method. For 0 l 0.7 fm, where l is the length of the subspace, the entropic c-function is almost constant, indicating conformally invariant dynamics. The value of the constant agrees with that perturbatively obtained from free gluons, with 20 % discrepan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 56 publications
5
47
0
Order By: Relevance
“…We found that, for fixed C, as we 11 For d = 2, the expression for renormalized entanglement entropy is similar to the entropic c-function [51]. The fact that c-function decreases monotonically from UV to IR has also been confirmed both in lattice as well as in holographic studies [52,53]. increase the number of spacetime dimensions the magnitude of the ratio S q /S 1 increases.…”
Section: Rényi Entropy From Ads-schwarzschild Black Holesupporting
confidence: 68%
“…We found that, for fixed C, as we 11 For d = 2, the expression for renormalized entanglement entropy is similar to the entropic c-function [51]. The fact that c-function decreases monotonically from UV to IR has also been confirmed both in lattice as well as in holographic studies [52,53]. increase the number of spacetime dimensions the magnitude of the ratio S q /S 1 increases.…”
Section: Rényi Entropy From Ads-schwarzschild Black Holesupporting
confidence: 68%
“…The entan-glement entropy of the selected domain A is defined as the von Neumann entropy of the reduced density matrix obtained by tracing out the degrees of freedom located out of domain A. The entanglement entropy is hard to compute in QCD, but it is suitable to compute it in the lattice [23][24][25], see also [26]. The entanglement entropy can be also evaluated at the gravity side.…”
mentioning
confidence: 99%
“…25. The "scaling factors" m SF x,y (z, z h , ν) and m EF x,y (z, z h , ν) defined by (5.22) and (5.23) and their UV approximations (5.20) and (5.21) shown by the dashed lines.The scaling functions m SF x,y and m EF x,y shown in(25) are defined by the formula similar to (5.18) and(5.19)…”
mentioning
confidence: 99%
“…There has been considerable progress in understanding the computation of entanglement entropy in lattice gauge theories, see for example [32,33,[37][38][39], and it would be interesting to explore how the continuum limit of such computations can be matched with our definition of renormalized entanglement entropy.…”
Section: Discussionmentioning
confidence: 99%